INCLUSIVITY AND DERADICALIZATION OF RELIGION - Islam, Muhammad Hifdil (Humanistika : Jurnal Keislaman, 2016)
AbstractClaims of absoluteness for each religion being enlarged by the differences between religions. Inclusive problem in Islam is a continuation of the thought or the idea of neo-modernism to a more specific area after pluralism, precisely in the field of theology[1] without leaving a space of tolerance in this field. For empathy or sympathy, how others perceive their own religion and we often judge the faith of others by seeing our own theology. To solve that we can use an external relations for the creation of religions, interreligious dialogue needs to be done. Then, in the internal religion,it is Â required a reinterpretation of religious messages more universal human touch. Problem formulation problems associated with it can be taken the following issue of religious inclusiveness relationship with the efforts of inter-religious harmony.Keywords: Inclusivity, Religion, Deradicalization[1] Nurcholish Madjid, Islam kemoderenan dan Keindonesiaan, (Jakarta: Mizan, 1997), hlm. 70